PEMBELAJARAN SAINS UNTUK ANAK SD/MI DENGAN PENDEKATAN SAINTIFIK - Supriyati, Supriyati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2015)
Learning is a process of the interaction of learners with educators and learning resources in a learning environment. At elementary school age children experience rapid growth both in the physical and intelligence. Science is knowledge that is verifiable by using scientific methods. The process skills and scientific attitude can be trained to learners to learn science. The nature of science is a product, process and scientific attitude. The process of learning with a scientific approach which touches three domains are cognitive, affective and psychomotor. Results of study with scientific approach makes students productive, creative, and innovative. Enhancement affective through the strengthening of attitudes, skills and integrated knowledge. Five basic learning experiences in the scientific approach is to observe, ask, gather information, associates, and communicate.